Basic system analysis - Palani S. Dr (Ane Books Ltd, 2014)
This book covers exclusively the syllabus content of II year (3rd Semester) of B.Tech. Electrical and Electronic Engineering of UPTU, Lucknow. A clear and comprehensive treatment of continuous time signals and system is given with numerical examples. Fourier series and Fourier transform play a very important role in signal analysis. These topics are discussed at length with numerical examples have been given wherever necessary. It is well known that Laplace transform method of analysis of linear time invariant system is popularly used in literature. An extensive application of this theory is also described in this book